The cytomegalovirus protein kinase pUL97: Host interactions, regulatory mechanisms and antiviral drug targeting - Steingruber, Mirjam; Marschall, Manfred (Microorganisms, 2020)
Human cytomegalovirus (HCMV) expresses a variety of viral regulatory proteins that undergo close interaction with host factors including viral-cellular multiprotein complexes. The HCMV protein kinase pUL97 represents a viral cyclin-dependent kinase ortholog (vCDK) that determines the efficiency of HCMV replication via phosphorylation of viral and cellular substrates. A hierarchy of functional importance of individual pUL97-mediated phosphorylation events has been discussed; however, the most pronounced pUL97-dependent phenotype could be assigned to viral nuclear egress, as illustrated by deletion of the UL97 gene or pharmacological pUL97 inhibition. Despite earlier data pointing to a cyclin-independent functionality, experimental evidence increasingly emphasized the role of pUL97-cyclin complexes. Consequently, the knowledge about pUL97 involvement in host interaction, viral nuclear egress and additional replicative steps led to the postulation of pUL97 as an antiviral target. Indeed, validation experiments in vitro and in vivo confirmed the sustainability of this approach. Consequently, current investigations of pUL97 in antiviral treatment go beyond the known pUL97-mediated ganciclovir prodrug activation and henceforward include pUL97-specific kinase inhibitors. Among a number of interesting small molecules analyzed in experimental and preclinical stages, maribavir is presently investigated in clinical studies and, in the near future, might represent a first kinase inhibitor applied in the field of antiviral therapy.
CRIS-Team Scopus Importer:2020-04-24
Keywords: Antiviral drugs; Cyclin/cyclin-dependent kinase complexes; Human cytomegalovirus (HCMV); Kinase-host interactions; Protein kinase pUL97; Regulatory mechanisms